Environmental Sustainable Development Target In Indonesia: A VECM Analysis - Basri; Herianti (Program Studi Magister Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Sunan Kalijaga, 2024)
Environmentally sustainable development is of utmost importance today. Amidst the global challenges of climate change and environmental degradation, Indonesia is facing an urgent situation to balance economic growth with environmental sustainability. This study examines the factors determining sustainable development targets in Indonesia using vector error correction models (VECM). This study uses economic and environmental data from 1992 to 2022 to analyze the relationship between energy consumption, urbanization, environmental policy stringency, and the environmental quality index. The tests used in this study include statistical tests, lag criterion tests, cointegration tests, VAR stability tests, and Granger causality tests. The study results indicate a long-term influence of the variables of energy consumption, urbanization, and environmental policy stringency on environmental quality. In the short term, urbanization has a significant positive effect on environmental quality in Indonesia. These findings emphasize the importance of strong environmental policy integration to mitigate environmental degradation and achieve sustainable development in Indonesia. Strategic policy recommendations for policymakers are to reduce the use of fossil fuels, switch to renewable energy, and implement a sustainable urbanization model by considering strategic urban spatial aspects.